Strategi Peningkatan Pendapatan Melalui Optimalisasi Tata Kelola Perusahaan Pada Wahana Agro Wisata Pelangi - Mardini, Dwi; Zulfatillah, Auliya (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study examines the implementation of corporate governance principles in the management of recreational facilities at Agro Wisata Pelangi, with a focus on their impact on operational performance and visitor satisfaction. Using a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate that the application of key governance principles— accountability, transparency, responsibility, and fairness—has contributed to structured organizational management, clear operational procedures, and regular financial reporting.   However, challenges remain in maintaining transparency, particularly in communicating information related to additional fees and safety measures to visitors. Strategic management that integrates agrotourism development with local community involvement has proven effective in optimizing revenue and enhancing visitor engagement. A positive correlation between effective governance and the increase in visitor numbers and financial outcomes underscores the importance of good corporate governance in the development of sustainable tourism.